KAJIAN PERSEPSI DAN POTENSI PENGEMBANGAN KAWASAN PARIWISATA PULAU KECIL STUDI KASUS: KAWASAN PANTAI PADANG MELANG KECAMATAN JEMAJA KABUPATEN NATUNA - Cahyadinata, Indra (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2008)
Small Islands are potential area to be developed becoming tourism area. Jemaja Island as one of the small islands have potency to be able to be developed, which recognized with Padang Melang area. This research is aimed to know perception of society regarding to development of the area and compile tourism potencies that can be developed. Method the used is descriptive method with SWOT analysis. Result of this research indicates that society very support development of tourism (with good perception). Tourism potency is able to be developed including coastal tourism, maritime tourism, natural tourism and history tourism. Development strategy that recommended involve settlement and development of package of tourism, development of tourism facility, adding local transportation facility, opening flight and applying of base on community development in development of tourism.